A convenient fluorescence sensor of tetracycline based on B, N codoped carbon dots/polymer composite film. (15th March 2022) - Hu, Yingying; Guan, Rentian; Zhang, Shuai; Fan, Xiaoyu; Liu, Wenjing; Zhang, Keying; Shao, Xiaodong; Li, Xia; Yue, Qiaoli
Highlights: B, N-doped CDs were prepared from 3-aminophenylboronic acid and citric acid. The bright blue fluorescence of CDs can be quenched effectively by TC. A convenient sensor of TC was constructed based on the CDs-PVA composite film. Abstract: A convenient fluorescence sensor of tetracycline (TC) was constructed based on carbon dots (CDs) and polyvinyl alcohol (PVA) hydrogel film. The immobilization of CDs in PVA carrier can stabilize the fluorescence of CDs by inhibiting the fluorescence quench due to the aggregation of CDs with time. CDs were prepared by a hydrothermal method. CDs showed bright blue fluorescence with the quantum yield of 0.35. The fluorescence of CDs was quenched by TC owing to the inner filter effect. The linear range for TC detection was 0–350 µM and the limit of detection was 0.17 µM. To test conveniently, PVA film was employed to upload CDs. Therefore, a novel sensor for TC was constructed in a visual mode. By comparison with the most of previous works, the present method displayed higher sensitivity and better selectivity. The results suggest that the present sensor has potential applications in the real-time detection of TC in food analysis.